Mediating Effect of Perceived Organizational Support on the Relationship between Leader-Member Exchange and the Innovation Work Behavior of Nursing Employees: A Social Exchange Perspective - Fahad Ahmed Qureshi; Qamar Zaman; Mubeen Butt (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
The present study aimed at investigating the relationship between Leader-Member Exchange and Innovative Work Behavior in Pakistani nursing sector. Additionally, the study examined the relationship between Leader-Member Exchange as an independent variable and dependent variable Innovative Work Behavior moreover it has examined the impact of Leader-Member Exchange and Innovative Work Behavior further this explored mediating role of Perceived Organization Support between Leader-Member Exchange and Innovative Work Behavior. The main study was conducted through systematic randomly selected sample of 400 nurses of ages between 24 and 60 belonging to public and private sector hospitals at Lahore. Survey method was used to collect data. Correlation analysis exposed the significance and strength of relationships between variables i.e. Innovative Behaviour, Perceived Organizational Support (POS) and Leader-Member Exchange (LMX). Moreover, regression analysis was performed for direct relationships. Baron and Kenny (1986) method are used for mediation analysis. The results showed that Perceived Organizational Support (POS) partially mediate between Leader-Member Exchange (LMX) and Innovative Behaviour. The LMX and POS, POS and IWB and LMX and IWB have significant relation which are 0.569(0.000),0.232(0.000) and 0.521(0.000).